Hubungan Kecanduan Smartphone Dengan Prokrastinasi Akademik Siswa - Fina Indah Putri; Ismawati Sitorus; Hubbal Khair; Novi Yanti; Syamsurizal Syamsurizal (Institut Agama Islam Sumatera Barat, 2023)
The research examines the problems of students who procrastinate both in working and Complete tasks even when time approaches deadline but still do not submit the task caused by spending more Some time to play smartphones. This study aims to determine the degree of addiction relationship Smartphones with academic procrastination of class students VIII. The method used is quantitative. Design The research taken in this study is correlation. The subjects used in this study amounted to 64 students class VIII Determination of samples used in research by using proportionate stratified technique random sampling. Measuring instruments used in this study is a scale made by the researcher himself which refers to the smartphone addiction scale and scale academic procrastination. Data analysis techniques that Used in this study is normality test, test linearity, and hypothesis testing. Results of this study shows that there is a significant relationship between smartphone addiction and procrastination academic in students. Then it can be concluded that The heavier the smartphone addiction, the higher academic procrastination of students, and vice versa The lighter the smartphone addiction, the more low academic procrastination of students.